Successful isolation of Leishmania infantum from Rhipicephalus sanguineus sensu lato (Acari: Ixodidae) collected from naturally infected dogs. Issue 1 (December 2015) - Medeiros-Silva, Viviane; Gurgel-Gonçalves, Rodrigo; Nitz, Nadjar; Morales, Lucia; Cruz, Laurício; Sobral, Isabele; Boité, Mariana; Ferreira, Gabriel; Cupolillo, Elisa; Romero, Gustavo
Abstract Background The main transmission route ofLeishmania infantum is through the bites of sand flies. However, alternative mechanisms are being investigated, such as through the bites of ticks, which could have epidemiological relevance. The objective of this work was to verify the presence ofLeishmania spp. inRhipicephalus sanguineus sensu lato collected from naturally infected dogs in the Federal District of Brazil. Methods Ticks were dissected to remove their intestines and salivary glands for DNA extraction and the subsequent amplification of the conserved region of 120 bp of kDNA and 234 bp of the hsp70 gene ofLeishmania spp. The amplified kDNA products were digested with endonucleases HaeIII and BstUI and were submitted to DNA sequencing. IsolatedLeishmania parasites from these ticks were analyzed by multilocus enzyme electrophoresis, and the DNA obtained from this culture was subjected to microsatellite analyses. Results Overall, 130 specimens ofR. sanguineus were collected from 27 dogs.Leishmania spp. were successfully isolated in culture from five pools of salivary glands and the intestines of ticks collected from four dogs. The amplified kDNA products from the dog blood samples and from the tick cultures, when digested by HaeIII and BstUI, revealed the presence ofL. braziliensis andL. infantum. One strain was cultivated and characterized asL. infantum by enzyme electrophoresis. The amplified kDNA products from the blood of one dog showed a sequence homology withL. braziliensis ; however, the amplified kDNA from the ticks collected from this dog showed a sequence homology toL. infantum. Conclusion The results confirm that the specimens ofR. sanguineus that feed on dogs naturally infected byL. infantum contain the parasite DNA in their intestines and salivary glands, and viableL. infantum can be successfully isolated from these ectoparasites.